A Case of Pincer Nail Successfully Treated with Tazarotene 0.1% Gel - Laura Vollono; Ester Del Duca; Sara Mazzilli; Luca Bianchi; Terenzio Cosio; Caterina Lanna; Elena Campione (Karger Publishers, 2020)
Pincer nail is a common condition characterized by excessive transverse nail curvature, progressively pinching the nail bed distally, resulting in cosmetic discomfort, pain and functional limitation. Treatment is difficult and often unsatisfactory. Surgical treatment performed by experienced physicians provides good outcomes. However, patients usually hesitate to undergo invasive procedures, preferring conservative treatments. Unfortunately, these mainly offer only temporary relief and recurrence rate is high. Topical tazarotene has been used in several nail conditions, but its potential remains not fully elucidated. We herewith present a case of pincer nails in a 35-year-old woman successfully treated with tazarotene 0.1% gel applied topically twice a day for 3 months who did not experience recurrence at 1-year follow-up. At 1-year follow-up, no recurrence has been observed. To our knowledge, this is the first case of pincer nails successfully treated with tazarotene 0.1% gel. With our report, we suggest topical tazarotene as a novel, effective conservative treatment of milder cases of this common, albeit disturbing condition. Although our report may not be sufficient to generalize the results, it paves the way for larger studies investigating the potential of this fast, noninvasive therapeutic agent.